Primary Endometrial Marginal Zone Lymphoma (MALT Lymphoma): A Unique Clinicopathologic Entity. (September 2016) - Bennett, Jennifer A.; Oliva, Esther; Nardi, Valentina; Lindeman, Neal; Ferry, Judith A.; Louissaint, Abner
Abstract : Primary lymphoma of the endometrium is exceptionally rare. Several cases of distinctly nodular lymphoid proliferations confined to the endometrium have previously been described and reported as lymphomas of mucosa-associated lymphoid tissue (MALT). We report the largest series (n=8) of these lymphomas, further defining their morphologic, immunohistochemical, and molecular spectrum. Patients ranged in age from 50 to 87 (median, 62) years. None had a prior history of lymphoma, and lesions were incidental in all but 1 in which a polyp was noted on macroscopic examination. Nodules ranged from small, round, and uniform with minimal architectural effacement to large, expansile, and coalescing with foci of diffuse growth. In the majority, the nodules were confined to the endometrium; however, 2 cases showed myometrial involvement, 1 of which also had extensive extrauterine disease. The nodules comprised monomorphic populations of mature CD20 + B lymphocytes with pale scant cytoplasm, CD43, BCL2, and IgM coexpression, and absence of CD10, CD23, and IgD expression. The nodules were associated with CD21/CD23 + follicular dendritic meshworks. Clonality was detected in 6 lesions, in 4 by polymerase chain reaction for clonal IGH rearrangement and in 3 by in situ hybridization for immunoglobulin light chains. All were negative for IGH and MALT1 rearrangements by fluorescence in situ hybridization. None of the patients received additional therapy after resection, and most (7/8) are alive with no evidence of disease at last follow-up (mean 4.2 y), whereas the remaining patient is alive with stable disease. These findings demonstrate the unique clinical and pathologic features that characterize primary MALT lymphoma of the endometrium. Abstract : Supplemental Digital Content is available in the text.